Effects of Installation Error on Tooth Surface Contact Characteristic of a Nutation Drive with Double Circular-arc Spiral Bevel Gear - Qin Chen; Yinkun Huang; Chao Jia; Ligang Yao; Jun Zhang (Jixie chuandong)
The contact characteristics of a nutation drive with double circular-arc spiral bevel gears are extremely sensitive to installation errors. To reveal the effects of installation errors on contact characteristics，the tooth surface contact analysis of double circular-arc spiral bevel gear with installation error is carried out. Firstly，the tooth surface equation of nutation drive double circular-arc spiral bevel gear in internal meshing form is derived. Secondly，the contact trace and geometric transmission error of the gear pair are obtained by using the tooth contact analysis （TCA）. Finally，the influence of the cone point errors of inner and outer bevel gears and the axis angle errors of the gear pair on the contact characteristic of the tooth surface of the double circular-arc spiral bevel gear pair is analyzed by numerical examples. The research show that with the increase of various installation errors，the contact trace deviates from the tooth height accordingly. The deviations of contact trace on the convex and the concave tooth surfaces from the tooth height direction are different in terms of sensitivity to installation errors. A positive installation error may have a stronger impact on the transmission error than a negative installation error. Based on the present founding，the installation errors of a nutation drive double circular-arc spiral bevel gears should be reasonably controlled to obtain an ideal meshing performance.